CHINA IN CENTRAL ASIA: GEOPOLITICAL, ECONOMIC, AND SOCIOCULTURAL VECTORS OF INFLUENCE - RYAZANTSEV, Sergey; VAZIROV, Zafar; PISMENNAYA, Elena; DELOVAROVA, Leila (CENTRAL ASIA AND THE CAUCASUS, 2019)
China’s economic, sociocultural, geopolitical, and ethnoreligious influence in Central Asia and the factors behind it. They examine the specifics of Chinese, Central Asian, and Russian demography and analyze the impact of socioeconomic and demographic processes of the recent years on China’s foreign policy. Having analyzed the volumes, dynamics, branch and regional specifics of China’s investments in Kazakhstan, Kyrgyzstan, Uzbekistan, Tajikistan, and Turkmenistan, the authors conclude that they can be described as a new form of realization of China’s geopolitical interests in Central Asia and Russia. They have identified new forms of Chinese migration in the context of China’s expanded investments beyond its borders, involvement of Chinese citizens in the “golden visa” programs in Europe and Mediterranean countries, and revealed that, more likely than not, labor migrants follow the flows of Chinese money and business migrants, consolidating the economic and geopolitical aspects of Beijing’s foreign policy. The authors have discussed the geopolitical, sociocultural, and economic role of Chinese diasporas in promoting the interests of their homeland and pointed out that the forms of Chinese influence in the world have become more varied.